Comparative morphological and histochemical studies on the follicular atresia in the goat and sheep ovary - GURAYA, S S; MONGA, S; KAUR, P; SANGHA, G K (The Indian Journal of Animal Sciences, 2013)
Comparative morphological and histochemical studies have been made of follicular atresia in the ovaries of goat and sheep. The atretic follicles were classified as preantral (early and late) and antral (Ia, Ib, IIa and IIb) follicles. In hoth preantral and antral atretic follicles, thecal hypertrophy was more conspicuous in the goat ovary than in sheep ovary. Sudanophillic lipids showed differential distribution in granulosa cell layers. The enzyme 3 B-HSDH activity increased in antral follicles. becoming intense in the hypenrophied thecae or interstitial gland cells of goat. Our resutis are compared and contrasted with those on other mammalian species. and possible physiological Signiricance is discussed.